2020
DOI: 10.1002/er.5337
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on water recovery and SO 2 permeability of ceramic membranes with different pore sizes

Abstract: Summary In this study, the water recovery performance from flue gas with ceramic membrane tubes of different pore sizes 30, 50, and 200 nm was experimentally studied. The effects of flue gas temperature, flue gas flow rate, water coolant temperature, and water coolant flow rate on the water recovery performance were analyzed. In addition, in the experimental study of SO2 permeability, the pH of the water coolant inlet and outlet was measured using a pH meter to analyze the SO2 permeability of ceramic membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…The exact mechanism of this selectivity is unknown, but it could be attributed to higher preferential condensation of water vapor within the membrane pores. The work by Cheng et al [ 48 ] reported similar trends.…”
Section: Transport Membrane Condenserssupporting
confidence: 54%
See 1 more Smart Citation
“…The exact mechanism of this selectivity is unknown, but it could be attributed to higher preferential condensation of water vapor within the membrane pores. The work by Cheng et al [ 48 ] reported similar trends.…”
Section: Transport Membrane Condenserssupporting
confidence: 54%
“…The quality of recovered water depends on its ability to reject NO X and SO X contaminants. Several works investigated SO x flux in the TMC process [ 6 , 48 , 56 ]. Although flue gas passes through an FGD unit, it still contains ppm-level NO x and SO x contaminants.…”
Section: Transport Membrane Condensersmentioning
confidence: 99%
“…In addition, compared with the mesoporous ceramic membranes used in some studies, 27,30,53 the macroporous ceramic membranes used in this experiment can eliminate a condensate film at a lower transmembrane pressure difference (below 20 kPa) because of the higher water permeability produced by large pores. The result indicates that ceramic membranes with superior permeability should be developed for moisture recovery to reduce energy consumption.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 13 , with flue gas temperature increases, the recovered water flux increases in an approximate parabolic form. That is, the higher the flue gas temperature is, the faster the growth rate of recovered water flux is due to the water vapor content increasing exponentially with an increasing flue gas temperature at a certain flow rate [ 47 ]. However, the flue gas enthalpy value increases with the increase of flue gas temperature.…”
Section: Resultsmentioning
confidence: 99%